2009
DOI: 10.1111/j.1349-7006.2009.01228.x
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive activation of nuclear factor‐κB is preferentially involved in the proliferation of basal‐like subtype breast cancer cell lines

Abstract: Constitutive nuclear factor (NF)-kB activation is thought to be involved in survival, invasion, and metastasis in various types of cancers. However, neither the subtypes of breast cancer cells with constitutive NF-kB activation nor the molecular mechanisms leading to its constitutive activation have been clearly defined. Here, we quantitatively analyzed basal NF-kB activity in 35 human breast cancer cell lines and found that most of the cell lines with high constitutive NF-kB activation were categorized in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
140
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 129 publications
(151 citation statements)
references
References 35 publications
10
140
1
Order By: Relevance
“…Clinical trials of EGFR inhibitors for metastatic TN breast cancer are under way, and MD Anderson is initiating a phase II study with panitumumab as part of the preoperative chemotherapy regimen for patients with primary IBC without HER-2 overexpression. Other possible agents that may be tested for TN disease include Hedgehog inhibitors, the Src kinase inhibitor dasatinib, the mammalian target of rapamycin inhibitor everolimus [26], and inhibitors of nuclear factor-B [27], cyclin E, and Skp2 [28]. Given the poor survival rates associated with IBC despite the advent of trimodality therapy (5-year OS, 59%), new IBCspecific molecular targets are being sought to improve the outcome of patients with IBC.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical trials of EGFR inhibitors for metastatic TN breast cancer are under way, and MD Anderson is initiating a phase II study with panitumumab as part of the preoperative chemotherapy regimen for patients with primary IBC without HER-2 overexpression. Other possible agents that may be tested for TN disease include Hedgehog inhibitors, the Src kinase inhibitor dasatinib, the mammalian target of rapamycin inhibitor everolimus [26], and inhibitors of nuclear factor-B [27], cyclin E, and Skp2 [28]. Given the poor survival rates associated with IBC despite the advent of trimodality therapy (5-year OS, 59%), new IBCspecific molecular targets are being sought to improve the outcome of patients with IBC.…”
Section: Discussionmentioning
confidence: 99%
“…The preparation of recombinant adenoviruses was performed as described previously (11). RNA samples were prepared from MDA-MB-436 cells 24 hours after infections.…”
Section: Microarray Analysis For Identification Of Nf-kb Target Genesmentioning
confidence: 99%
“…Accumulating evidence indicates that aberrant NF-kB activation leads to tumorigenesis and cancer malignancy through the expression of genes involved in survival, metastasis, and angiogenesis (6,10). We have previously reported that TNBCs undergo constitutive and strong activation of NF-kB, whose activation is transient in normal cells upon various physiologic stimuli (11,12). Furthermore, the adenovirus-mediated expression of a nondegradable IkBa super-repressor (IkBaSR), in which Ser-32 and Ser-36 (the residues phosphorylated by IKKb) were substituted with alanine, blocked NF-kB activation, and thereby inhibited the growth of several TNBC cell lines.…”
Section: Introductionmentioning
confidence: 99%
“…We recently reported that (−)-DHMEQ, a specific NF-κB inhibitor, induced anoikis and inhibited peritoneal metastasis in pancreatic cancer cells [11]. It has been shown that constitutive NF-κB activity is detected in breast cancer cell lines, and is preferentially involved in the proliferation of the basal-like (triple-negative) subtype [12]. Previous studies showed that nuclear NF-κB/p65 expression was a predictive factor of resistance to neoadjuvant chemotherapy in breast cancer [13,14].…”
Section: Introductionmentioning
confidence: 99%